Energy-restricted, high-protein diets more effectively impact cardiometabolic profile in overweight and obese women than lower-protein diets. Issue 2 (April 2017) - Mateo-Gallego, Rocío; Marco-Benedí, Victoria; Perez-Calahorra, Sofía; Bea, Ana M.; Baila-Rueda, Lucía; Lamiquiz-Moneo, Itziar; de Castro-Orós, Isabel; Cenarro, Ana; Civeira, Fernando
Summary: Background & aims: High-protein energy-restricted diets have demonstrated efficacy in promoting weight loss in overweight and obesity. However, the protein percentage that achieves optimal efficacy and acceptability remains unknown. We sought to assess the effects of three energy-reduced diets with different percentages of calories from protein (20%, 27%, and 35%) on weight loss and lipids. Secondary outcomes included diet acceptability and compliance. Methods: Six-month, randomized study included women aged 18–80 years with BMI of 27.5–45 kg/m 2 and who were not taking lipid-lowering drugs. We randomly assigned 91 women to one of three calorie-reduced diets with: protein, 20%, 27%, or 35% (80% from animal protein); carbohydrates, 50%, 43%, or 35%; fat, 30%. Dietary intervention involved individual visits with a nutritionist every 2 weeks during the first 3 months. We performed a follow-up visit at 6 months. Results: Eighty women aged 44.0 ± 9.08 years with BMI of 37.7 ± 3.39 kg/m 2 completed the study. At 3 months, weight loss was −8.16 ± 4.18 kg, −9.66 ± 5.28 kg, and −10.7 ± 4.28 kg in the 20%, 27%, and 35%-protein groups, respectively ( P = 0.16). These figures slightly and homogeneously increased at 6 months. Around 65% of women following 35%-protein diet lost ≥10% of body weight vs. ∼33% in 20%-protein group ( P = 0.023). Significant decreases occurred in fat mass, lipids and insulin resistance, especially in the 35%-protein group ( P < 0.05 vs. 20% protein). This improvement was not fully explained by weight loss. Triglyceride change was negatively correlated with animal-protein intake. All groups provided similar responses to an acceptance, palatability, and satisfaction questionnaire. Conclusions: An energy-restricted diet with 35% protein, mostly of animal origin, more effectively impacts cardiometabolic profile than an energy-restricted diet with lower protein content although no clear benefit between diets in terms of overall weight loss was observed. The high-protein diet displayed an excellent safety profile and acceptability. This trial was registered in ClinicalTrials.gov asNCT02160496 . Clinical trial registration: The clinical trial has been registered in ClinicalTrials.gov (Identifier:NCT02160496 ).